KARAKTERISTIK DAN KETERAMPILAN KEPEMIMPINAN PENDIDIKAN - Realitawati, Realitawati; Ikrom, Fadhli Dzil (Journal of Professional Elementary Education, 2024)
The purpose of this study was to determine the extent to which the characteristics and educational leadership skills of the Principal of SD Plus Mutiara Insani Purwakarta. This study uses a descriptive qualitative research method using a questionnaire containing statement questionnaires and processed by describing or giving an overview of the object under study through data or samples that have been collected as they are. The target respondents were several teachers at SD Plus Mutiara Insani Purwakarta. The results of this study will show what characteristics and educational leadership skills are used by the principal of SD Plus Mutiara Insani and will be adjusted to the theories that the authors describe in this article